2010
DOI: 10.1016/j.jbi.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Showing Your Work: Impact of annotating electronic prescriptions with decision support results

Abstract: e-Prescribing systems with decision support do not routinely communicate an adequate amount of information regarding the prescribers' decision to pharmacists. To address this communication gap in the e-prescribing process, we implemented a system called Show Your Work (SYW) that appends alerts and override comments to e-prescriptions generated by an e-prescribing system. To assess the quantitative impact of this system, we conducted a randomized, double-blinded, controlled study to assess pharmacy callback rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…24 Over time, the potential of e-prescribing to improve safety, quality, and efficiency in primary care settings during patient care was recognized and recommended by policy makers. 1,25 It was assumed that this technology would lead to a significant improvement in safety in the process of prescribing and dispensing medications 24 even though improvement in patient safety and cost benefits are not well established or understood in ambulatory practice. 26,27 …”
Section: Introductionmentioning
confidence: 99%
“…24 Over time, the potential of e-prescribing to improve safety, quality, and efficiency in primary care settings during patient care was recognized and recommended by policy makers. 1,25 It was assumed that this technology would lead to a significant improvement in safety in the process of prescribing and dispensing medications 24 even though improvement in patient safety and cost benefits are not well established or understood in ambulatory practice. 26,27 …”
Section: Introductionmentioning
confidence: 99%
“…If you have decided after careful evaluation that the benefits of prescribing a medicine singly or in combination with other medicines outweigh the risks and elect to override an alert, then this should be clearly documented in the patient record and highlighted on the prescription. 5 • Give specific instructions when prescribing. For example, instructions such as "as directed", "as required" or "prn"…”
Section: Recommendations For Optimal Use Of Cdssmentioning
confidence: 99%
“…34 Finally, a recent article demonstrated the power of annotating electronic prescriptions with the actual calculation leading up to the dose. 35 …”
Section: Decreased Preventable Adverse Drug Eventsmentioning
confidence: 99%
“…44,45 In pediatrics, e-prescribing can improve communication through both improving clarity of prescriptions and providing standardized information about indications for therapy, rationales for overriding allergy alerts, and the weight-based calculations leading to a specific dose. 35 For all patients, e-prescribing systems can improve communication about provider willingness to allow generic substitution, [46][47][48] which, by avoiding higher copayments, can improve medication adherence. 49 A study on prescriptions 35 demonstrated the value of including body weight and the process associated with calculating a dose.…”
Section: Improved Communicationmentioning
confidence: 99%
See 1 more Smart Citation